Integrating Quadratus Lumborum and Transabdominal Plane Blocks for Effective Pain Management in Colon Cancer: A Case Report - Shallahudin, Shallahudin; Laksono, Ristiawan Mudji; Siswagama, Taufiq Agus; Asmoro, Aswoco Andyk (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2025)
Background: The Quadratus Lumborum Block (QLB) is an ultrasound-guided posterior abdominal wall block that targets the interfascial plane. This case report investigates the concurrent application of QLB and transabdominal plane block for pain management in a patient with colon cancer-related pain.Case Illustration: A 53-year-old male patient presented with abdominal pain at the site of an abdominal stoma and his back over the past 3 months. The pain was characterized as sharp and exacerbated by movement. Laboratory tests revealed leukocytosis and a prolonged activated partial thromboplastin time. A 2022 CT scan indicated a residual mass in the transverse colon with associated fat stranding involving the adjacent ileal wall. The patient was diagnosed with cancer-related pain due to colon cancer, and a comprehensive pain management plan involving the combination of QLB, transabdominal plane block, and a Durogesic patch (12.5 mcg/3 days) was devised. The abdominal pain significantly diminished, with an initial resting Numerical Rating Scale (NRS) score of 5-6 and an initial exacerbated NRS score of 7-9, reducing to a final resting NRS score of 1-2 and a final exacerbated NRS score of 2-3 after administering the pain management regimen: QLB with Ropivacaine 0.375% + Methylprednisolone injection 62.5 mg, totaling 20 cc, along with transabdominal plane block using Ropivacaine 0.375% with a total volume of 10 cc. No occurrences of nausea or vomiting were reported.Conclusion: Employing a combined approach of QLB and transabdominal plane block for pain management holds the potential to alleviate acute and chronic pain while facilitating a robust post-operative recovery. Further research involving a larger patient population is warranted to explore the full efficacy and effectiveness of the QLB technique.